Pendampingan Pemanfaatan Sistem Informasi Manajemen dalam Pengelolaan Data Peserta Didik di SMP Al Munawwaroh Rejoso - Deden Ramdhani (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to provide assistance in utilizing the Management Information System (MIS) for managing student data at Al Munawwaroh Rejoso Junior High School. The partners in this activity are school operators who directly handle student data administration. The implementation methods include initial observation, training, technical assistance, and evaluation of the results. The assistance process focuses on the use of the EMIS system and other school support platforms, utilizing available devices such as laptops and the internet. The results of the activity show that this assistance has helped improve the understanding and skills of school operators in inputting, processing, and presenting student data more effectively and accurately. In addition, the availability of facilities, good planning, and internal monitoring support also strengthened the quality of school data management. With the optimal implementation of the Management Information System, SMP Al Munawwaroh Rejoso was able to produce faster, more accurate, and more structured administrative reports, thereby supporting improvements in the quality of educational services and facilitating the monitoring of student development.